Synthesis of Chromeno[4,3-b]pyrrol-4(1H)-ones, from β-Nitroalkenes and 4-Phenylaminocoumarins, under Solvent–free Conditions - Padilha, Gustavo (2017)
A new approach toward chromeno[4,3-b]pyrrol-4(1H)-ones, by annulation of 4-phenylaminocoumarins with β-nitroalkenes, is reported and its conditions were optimized. The transformations under the fine-tuned conditions took place under promotion by TsOH.H2O, in the absence of solvent. The scope and limitations of the process were explored, by systematic modification of two diversification points. A reaction mechanism, triggered by a Michael addition of the nitrogen moiety of the 4-phenylaminocoumarins to the β-nitroalkene, was also proposed. Further functionalization of a selected tricycle was performed; the photophysical (UV and fluorescence spectra; 1O2 generation) and electrochemical (cyclic voltammetry) properties of some heterocycles were studied.